Couples’ mental health and increased Instagram consumption - Khanam, Swaleha; Parihar, Tasha Singh (Comunicação Mídia e Consumo, 2024)
This study looks at how Instagram affects couples’ mental health in the digital age, highlighting both its benefits and drawbacks. Instagram has one billion active users per month, making it the most popular platform for sharing content that involves images. It talks about the possible negative effects of using Instagram, such as low self-esteem, cyberbullying, and social comparison. The study advises couples to set reasonable limits, use Instagram with awareness, and be open and honest about their online relationships. To support couples in navigating the digital world while placing a high priority on their mental health, mental health professionals should include discussions on digital dynamics in couple’s therapy sessions. Instagram may have a detrimental effect on a couple’s mental health by encouraging social comparison, jealousy, problems with trust, and excessive social media use. It can foster understanding and bring up pleasant memories, but it can also result in miscommunication and emotional distance. Although there is little data linking Instagram use to mental health, research has indicated that using the platform to browse Instagram might lessen loneliness while influencers’ popular practice of broadcasting on the platform can make people feel more alone. Instagram and other picture-based platforms can help users establish a more robust social presence, which increases their effectiveness in reducing loneliness. The study identifies methodological difficulties in examining the mental health of spouses and makes recommendations for further research. It also covers relationship growth, social comparison dynamics, communication styles, and privacy concerns, as well as the ramifications for couples and therapists. It calls for more research and professional development to address the evolving digital couple’s therapy landscape. The present study concludes by examining the impact of Instagram on mental health in a range of age groups and highlighting areas that require more investigation or development to alleviate the negative impacts of social media use on mental health.